Baitul Mal dan Kontribusinya terhadap Pendidikan Anak Yatim dan Fakir Miskin di Kota Subulussalam (Studi Pada Baitul Mal Kota Subulussalam) - Rosmaini Rosmaini; Warul Walidin; Saifullah Idris (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
The aims of this research are: (1) To find out the contribution made by Baitul Mal Kota Subulussalam to the Religious Education of orphans and the poor; (2) To find out the What programs are carried out by the Baitul Mal of Subulussalam City to help Islamic education for orphans and the poor; (3) To find out the What are the supporting and inhibiting factors of Baitul Mal Kota Subulussalam in distributing zakat for the Islamic religious education program for orphans and the poor. This study used a qualitative descriptive research method with data collection techniques through interviews, observation, and documents. Data analysis techniques use data reduction, data display, and conclusions or verification. The findings of this research are the contributions made by Baitul Mal Kota Subulussalam: providing compensation in the form of educational scholarships, assisting with operations for Islamic boarding schools, religious teachers, mosques/mushallas, and other da'wah institutions so that it is easy to implement Islamic religious education in a social environment, forming assisted groups for productive businesses through Al-Qord financing. Forming social movements such as compensation for orphans and dhuafa, assistance with basic needs, and free breakfast on Fridays (Blessing Fridays). Providing medical assistance to the poor in the form of medical expenses, accommodation, and others. Factors inhibiting the contribution of Baitul Mal Kota Subulussalam are the low awareness of the community, the lack of awareness of paying zakat from the community is one of the obstacles in managing zakat funds so that they can be efficient in the economy.